Geogebra como ferramenta auxiliar no processo de aprendizagem de números primos na educação básica - LOPES, Yale de Ângelis (2017)
The present dissertation seeks to enrich and encourage the learning of prime numbers by high school students. In order to do so, we model the technique of RSA Cryptography and the Sieve of Eratosthenes using the GeoGebra application to serve as an auxiliary didactic material in the teaching-learning process of prime numbers. We started this paper with a presentation of the PCNEM (main guiding document of the High School curriculum) and also some papers with affinity with the theme of this dissertation. Some basic concepts of Number Theory are also presented once they are necessary for understanding the RSA technique. In this paper we not only show how our constructions in GeoGebra work, but also how they were thought and elaborated.